Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5606/ehc.2019.66489
|View full text |Cite
|
Sign up to set email alerts
|

Is pelvic mapping applicable in iliosacral screw fixation to determine screw entry point and screw trajectory?

Abstract: Pelvis injuries account for approximately 3% of all skeletal injuries. [1] In unstable fractures, morbidity and mortality rates are particularly high, requiring surgery to provide stability and prevent potential morbidities and mortality. [2] In posterior pelvis fractures and dislocations, surgery can be performed with an open or percutaneous approach; however, the latter has become the preferred mode of treatment in recent years. [3,4] ÖZ Amaç: Bu çalışmada, iliyosakral vida sabitlemede vida giriş noktası ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It should be remembered that there are morphological changes in the sacrum described as normal. We can see this best in the study conducted by Goetzen et al (15). In this study, it is reported that the screw insertion location may change depending on the sacrum types, especially in the lateral projection.…”
Section: Discussionmentioning
confidence: 79%
“…It should be remembered that there are morphological changes in the sacrum described as normal. We can see this best in the study conducted by Goetzen et al (15). In this study, it is reported that the screw insertion location may change depending on the sacrum types, especially in the lateral projection.…”
Section: Discussionmentioning
confidence: 79%
“…Several researchers have attempted to define a safe starting point on the sacral lateral view. Durusoy et al defined a starting point located in the shadow of the S1 sacral canal, which was posterior to the sacral body 7 . Javidmehr et al chose the posteroinferior quadrant of the anterosuperior quadrant of the S1 body to set the starting point 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The reasoning is that the ICD serves to indicate the slope of the sacral ala, allowing it to serve as a reliable guide that prevents anterior penetration of the sacrum, which would endanger the L5 nerve root 5,6 . Notably, the S1 shadow (which is posteroinferior to the ICD) is a region (rather than a specific point) in which the SI iliosacral screw starting point can be set at the surgeons' discretion [7][8][9][10][11] , which limits the reproducibility of the procedure. Given that sacral dysmorphism (Fig.…”
mentioning
confidence: 99%
“…[ 9 , 10 ] However, patients may be prone to develop complications due to some factors, including variability in pelvic anatomy, the narrowness of the bone corridor to be screwed, and inadequacies in imaging and surgical procedures. [ 11 ] In the literature, the current technique has been modified by combining with different imaging techniques in order to decrease the complication rates and increase surgical success. Computed tomography (CT) and computerized navigation systems are the most common combinations introduced for this purpose.…”
Section: Introductionmentioning
confidence: 99%